(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The study was carried out in four major maize growing areas namely Chuadanga, Dinajpur, Bogra and Lalmonirhat during 2006-2007 to know profitability level of maize production in Bangladesh. A total of 200 randomly selected maize growers taking 50 from each location were interviewed using pre-designed interview schedule. The average yield was found to be 8.00 t/ha. The average costs of maize production were Tk 44197, Tk 33195 and Tk 24441 per hectare on total cost, variable cost and cash cost basis respectively and gross return was Tk 69773 per hectare. The gross margin was Tk 36578/ha on total variable cost (TVC) and Tk 45332/ha on cash cost basis. The net return was observed to be Tk 25575 per hectare. Benefit cost ratios were calculated as 1.58, 2.10 and 2.85 on total cost, variable cost and cash cost basis respectively. As a result, maize cultivation was more profitable. Lack of capital and high price of TSP were the main constraints to its higher production. Key Words: Maize; production; agro-economic. DOI: 10.3329/bjar.v34i1.5748 Bangladesh J. Agril. Res. 34(1) : 15-24, March 2009